Restorative justice in the Ecuadorian criminal system: An urgent need for its implementation - Ramírez Zamora , Andrea Giomar (2025)
The article analyzes the deficiencies of the traditional model based on oppression and punishment, and proposes restorative justice as an alternative tool for conflict resolution. The objective is to evaluate how restorative justice could mitigate the deficiencies of the penal system, benefiting victims and offenders. To do so, a qualitative approach is used, the design is documentary and analytical-synthetic, inductive, comparative legal and exegetic methods are applied. The results indicate that restorative justice is an important resource in relation to the Ecuadorian penal system, even more so in cases where mediation is more advantageous than the adversaria system. However, there are obstacles such as the absence of precise instructive norms and the lack of training for justice operators. It is concluded that restorative justice acts in the compensation of the damage caused and in reconciliation, being of great contribution to social peace and balance in society.